Toxicity of Cadmium (Cd) and Copper (Cu) on Growth of Microalgae Isochrysis galbana and chlorophyll- a Content - Sembiring, Herbin; Nurrachmi, Irvina; Hindarti, Dwi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The research was conducted from Mei until June 2019 at the Laboratory of Marine Chemistry and Ecotoxicology, Research Center of Oceanography, Indonesian Institute of Sciences, Jakarta. The purpose of this research was to determine the 96-h IC50, LOEC, NOEC and the chlorophyll-a content after the exposure of cadmium and copper to microalgae I. galbana. The result showed that the response due to the treatmeant given is not from the influence of water quality parameters, the 96-h IC50 value of cadmium and copper for growth of I. galbana was 1.3706mg/l and 0.0117 mg/l, respectively the LOEC cadmium and copper was 0.32 mg/l and 0.0056 mg/l, the NOEC cadmium and copper was <0.32 mg/l and<0.0056 mg/l. Based on data IC50, cooper was more toxic than cadmium to the microalgae I. galbana. The chlorophyill-a content correlates with the percent decrease in microalgae cell density. Keyword :IC50, LOEC, NOEC, I. galbana, Toxicyty